Calendar of Events. (Communications of the ACM, 2017)
The article presents a calendar of Association for Computing Machinery (ACM) events for February 2017, which include a Symposium on Principles and Practice of Parallel Programming, an International Conference on Web Search and Data Mining, and an International Workshop on Mobile Computing Systems and Applications.